2009
DOI: 10.1007/s11270-009-0139-0
|View full text |Cite
|
Sign up to set email alerts
|

Levels and Chemical Forms of Heavy Metals in Soils from Red River Delta, Vietnam

Abstract: Levels and chemical forms of heavy metals in forest, paddy, and upland field soils from the Red River Delta, Vietnam were examined. Forest soils contained high Cr and Cu levels that were higher in subsurface than in surface layers. Levels of Cu, Pb, and Zn that exceeded the limits allowed for Vietnamese agricultural soils were found in the surface layer of a paddy field near the wastewater channel of a copper casting village. High amounts of Zn accumulated in the surface soil of paddy fields close to a fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Top figure: Core R2, bottom figure: Core R4 local soil and water environments (Huong et al 2007). In addition, Phuong et al (2010) observed high concentrations of trace elements (Pb, Cu, Zn) in the top layers of rice paddy soils near smelting and recycling Pb and Zn factories. Moreover, they also showed that the intensive utilization of N-P-K fertilizer in agriculture, which often includes Zn, Cu, B, Mo, Co, and other trace elements, likely attributed to the high trace element concentrations in the soil environment.…”
Section: Historical Profiles Of Trace Element Concentrationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Top figure: Core R2, bottom figure: Core R4 local soil and water environments (Huong et al 2007). In addition, Phuong et al (2010) observed high concentrations of trace elements (Pb, Cu, Zn) in the top layers of rice paddy soils near smelting and recycling Pb and Zn factories. Moreover, they also showed that the intensive utilization of N-P-K fertilizer in agriculture, which often includes Zn, Cu, B, Mo, Co, and other trace elements, likely attributed to the high trace element concentrations in the soil environment.…”
Section: Historical Profiles Of Trace Element Concentrationsmentioning
confidence: 95%
“…Subsequently, a substantial quantity of these trace elements in the RRD watershed can be annually transported from the main waterway of the RR to coastal areas. The high concentrations of trace elements (Ag, Pb, Zn, Cu, V, Mn, Co, Cd, Sb, and Sn) in the mangrove sediments can therefore most likely be attributed to the discharge of untreated effluent from industrial activities (e.g., mechanical, chemical, zinc smelt, and steel works), and drainage from agriculture in the RRD (Huong et al 2007;Phuong et al 2010).…”
Section: Historical Profiles Of Trace Element Concentrationsmentioning
confidence: 99%
“…Metals from anthropogenic sources tend to be more mobile than pedogenic or lithogenic ones (Phuong et al 2010).…”
Section: Metal Fractionationmentioning
confidence: 99%
“…The mangrove forest environment and ecosystem have deteriorated due to pressures from economic development upstream [2,20,21]. Previous studies in the RRD showed that heavy metals accumulate in the top soil layer of the mangrove forest [20] and that trace metal concentrations vary with land use [22]. There are five main land uses in the estuary, but the heavy metal concentrations of soil under these land uses have not been reported.…”
Section: Introductionmentioning
confidence: 99%